Warm Climate Production Guidelines for Bougainvillea - Richard Schoellhorn; Erin Alvarez (EDIS)
This document is ENH 874, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date October 1, 2002.